2019
DOI: 10.1371/journal.pone.0210335
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dementia and ankylosing spondylitis: A nationwide, population-based, retrospective longitudinal cohort study

Abstract: Among a variety of comorbidities of ankylosing spondylitis (AS), the association between dementia and AS by using an extensive dataset from the Korean National Health Insurance System was evaluated in this study. We extracted 15,547 newly diagnosed AS subjects among the entire Korean population and excluded wash-out patients (n = 162) and patients that were inappropriate for cohort match (n = 1192). Finally, 14,193 subjects were chosen as the AS group, and through 1:5 age- and sex-stratified matching, 70,965 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
(55 reference statements)
0
20
1
3
Order By: Relevance
“…Two studies were conducted in Europe 16,17 and the other 2 were conducted in Asia. 18,19 All studies used administrative databases to identify AS and dementia. All of them were of good quality reflected by a Newcastle-Ottawa score of at least 7.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies were conducted in Europe 16,17 and the other 2 were conducted in Asia. 18,19 All studies used administrative databases to identify AS and dementia. All of them were of good quality reflected by a Newcastle-Ottawa score of at least 7.…”
Section: Search Resultsmentioning
confidence: 99%
“…Second, there was a high statistical heterogeneity in this meta-analysis which could be due to dissimilarity of study methodology (cohort vs case-control studies) and background population from each study. Interestingly, patients with AS in the study by Jang et al 18 had a significantly higher prevalence of comorbidities such as hypertension, diabetes mellitus, dyslipidemia and depression, which are known to be risk factors of dementia and may play roles as confounders. 13,[40][41][42] Finally, the small number of included studies could limit the ability to interpret the funnel plot.…”
Section: F I G U R E 2 Forest Plot Of the Meta-analysis Of Risk Of Dementioning
confidence: 96%
See 2 more Smart Citations
“…The only previous similar evidence that refers to a recent nationwide cohort study found that the prevalence of dementia in the AS group was significantly higher than those of the control group. 24 Also, cerebral functional deficits in patients with AS have already been observed in fMRI. 11 There are several possible explanations for cognitive impairment in patients with AS.…”
Section: Discussionmentioning
confidence: 96%